Soft tissue differentiation by diffuse reflectance spectroscopy - Zam, Azhar; Stelzle, Florian; Nkenke, Emeka; Tangermann-Gerk, Katja; Schmidt, Michael; Adler, Werner; Douplik, Alexandre (OSA trends in optics and photonics, 2009)
Laser surgery gives the possibility to work remotely which leads to high precision, little trauma and high level sterility. However these advantages are coming with the lack of haptic feedback during the laser ablation of tissue. Therefore additional means are required to control tissue-specific ablation during laser surgery supporting the surgeon regardless of experience and skills. Diffuse Reflectance Spectroscopy provides a straightforward and simple approach for optical tissue differentiation. We measured diffuse reflectance from four various tissue types ex vivo. We applied Linear Discriminant Analysis (LDA) to differentiate the four tissue types and computed the area under the ROC curve (AUC). Special emphasis was taken on the identification of nerve as the most crucial tissue for maxillofacial surgery. The results show a promise for differentiating soft tissues as guidance for tissue-specific laser surgery by means of the diffuse reflectance.<br